aboutsummaryrefslogtreecommitdiff
path: root/haddock-api/src/Haddock/Syb.hs
diff options
context:
space:
mode:
Diffstat (limited to 'haddock-api/src/Haddock/Syb.hs')
-rw-r--r--haddock-api/src/Haddock/Syb.hs55
1 files changed, 55 insertions, 0 deletions
diff --git a/haddock-api/src/Haddock/Syb.hs b/haddock-api/src/Haddock/Syb.hs
new file mode 100644
index 00000000..4847e486
--- /dev/null
+++ b/haddock-api/src/Haddock/Syb.hs
@@ -0,0 +1,55 @@
+{-# LANGUAGE Rank2Types #-}
+
+
+module Haddock.Syb
+ ( everything, everythingWithState, everywhere
+ , mkT
+ , combine
+ ) where
+
+
+import Data.Data
+import Control.Applicative
+
+
+-- | Perform a query on each level of a tree.
+--
+-- This is stolen directly from SYB package and copied here to not introduce
+-- additional dependencies.
+everything :: (r -> r -> r) -> (forall a. Data a => a -> r)
+ -> (forall a. Data a => a -> r)
+everything k f x = foldl k (f x) (gmapQ (everything k f) x)
+
+
+-- | Perform a query with state on each level of a tree.
+--
+-- This is the same as 'everything' but allows for stateful computations. In
+-- SYB it is called @everythingWithContext@ but I find this name somewhat
+-- nicer.
+everythingWithState :: s -> (r -> r -> r)
+ -> (forall a. Data a => a -> s -> (r, s))
+ -> (forall a. Data a => a -> r)
+everythingWithState s k f x =
+ let (r, s') = f x s
+ in foldl k r (gmapQ (everythingWithState s' k f) x)
+
+
+-- | Apply transformation on each level of a tree.
+--
+-- Just like 'everything', this is stolen from SYB package.
+everywhere :: (forall a. Data a => a -> a) -> (forall a. Data a => a -> a)
+everywhere f = f . gmapT (everywhere f)
+
+-- | Create generic transformation.
+--
+-- Another function stolen from SYB package.
+mkT :: (Typeable a, Typeable b) => (b -> b) -> (a -> a)
+mkT f = case cast f of
+ Just f' -> f'
+ Nothing -> id
+
+-- | Combine two queries into one using alternative combinator.
+combine :: Alternative f => (forall a. Data a => a -> f r)
+ -> (forall a. Data a => a -> f r)
+ -> (forall a. Data a => a -> f r)
+combine f g x = f x <|> g x